Digital Object Identifier (DOI): what is it, how does it work and how to use it? - Ferreira, Elisabete; Fuhr, Fabiane; Rodrigues de Lima, Karolayne Costa; Araujo, Paula Carina de [UNESP]; Pereira, Suzana Zulpo (Univ Federal Parana, Dept Ciencia & Gestao Informacao, 2015)
The members of the management team of the Digital Library of Academic Journals (BDP) of the Federal University of Parana (UFPR) presents the main concepts and clarify questions about the Digital Object Identifier (DOI).
Keywords: Digital Object Identifier (DOI); Persistent identifier; digital repositories